"Discrete peaks" of excitability and map overlap reveal task‐specific organization of primary motor cortex for control of human forearm muscles. Issue 12 (17th September 2017) - Massé‐Alarie, Hugo; Bergin, Michael J.G.; Schneider, Cyril; Schabrun, Siobhan; Hodges, Paul W.
Abstract: The primary motor cortex (M1) presents a somatotopic organization of body parts, but with overlap between muscle/movement representations. This distinct but overlapping M1 organization is believed to be important for individuated control and movement coordination, respectively. Discrete peaks of greater excitability observed within M1 might underpin organization of cortical motor control. This study aimed to examine interactions between M1 representations of synergist and antagonist forearm muscles, compare regions of greater excitability during different functional tasks, and compare characteristics of M1 representation recorded using surface and fine‐wire (fw ) electrodes. Transcranial magnetic stimulation (TMS) was applied over M1 for mapping the representation of 4 forearm muscles ( extensor carpi radialis brevis [ECRB], extensor digitorum communis, flexor carpi radialis, and flexor digitorum superficialis ) during three tasks: rest, grip, and wrist extension in 14 participants. There are three main findings. First, discrete areas of peak excitability within the M1 representation of ECRBfw were identified during grip and wrist extension suggesting that different M1 areas are involved in different motor functions. Second, M1 representations of synergist muscles presented with greater overlap of M1 representations than muscles with mainly antagonist actions, which suggests a role in muscle coordination. Third, as larger normalized map volume and overlap were observed using surface than fine‐wire electrodes, data suggest that cross‐talk from adjacent muscles compromised interpretation of recordings made with surface electrodes in response to TMS. These results provide a novel understanding of the spatial organization of M1 with evidence of "functional somatotopy." This has important implications for cortical control of movement. Hum Brain Mapp 38:6118–6132, 2017 . ©2017 Wiley Periodicals, Inc.